Simulation and Modeling Methodologies, Technologies and Applications - Pina, Nuno (Springer, 2015)
The present book includes extended and revised versions of a set of selected papers from the 1st International Conference on Simulation and Modeling Methodologies, Technologies and Applications (SIMULTECH 2011) which was sponsored by the Institute for Systems and Technologies of Information, Control and Communication (INSTICC) and held in Noordwijkerhout, The Netherlands. SIMULTECH 2011 was technically co-sponsored by the Society for Modeling & Simulation International (SCS), GDR I3, Lionphant Simulation and Simulation Team and held in cooperation with ACM Special Interest Group on Simulation and Modeling (ACM SIGSIM) and the AIS Special Interest Group of Modeling and Simulation (AIS SIGMAS).